"Methodological and epistemological challenges for the chiropractic profession in health care - a study of the history, status quo and future of research and clinical practices." - Myburgh, Corrie (Stellenbosch : University of Stellenbosch, 2011)
Thesis (DPhil)--University of Stellenbosch, 2005.